STRUMA OVARII WITH LITERATURES REVIEW (Iraqi Journal of Medical Sciences, 2016)
Struma ovarii is a highly specialized form of ovarian teratoma, characterized by the presence- entirely or predominantly- of mature thyroid tissue. Its most important complications, although rare, are malignant transformation and thyrotoxicosis. In the present 'case report' we describe a case of a 25 year old married woman that seeks medical advice for recurrent lower abdominal discomfort. The diagnosis of complex ovarian cyst confirmed by ultrasound examination of the abdomen, the operative findings were multilocular ovarian cyst treated by oophrectomy. The histological examination demonstrated typical elements of mature thyroid tissue that confirmed the diagnosis of struma ovarii.Keywords: ovarian teratoma, struma ovarii, thyroid tissue
Keywords: ovarian teratoma; struma ovarii; thyroid tissue